Discourse analysis of corporate codes of ethics : a thesis presented in partial fulfilment of the requirements for the degree of Doctor of Philosophy in Accountancy at Massey University, Manawatū, New Zealand - Chua, Frances Cho-Kwai (Massey University, 2015)
Ethics has always been an important element in economic activities. Ethical guidelines in the form of values, beliefs, norms, guidelines and rules have been developed over the years to set boundaries for appropriate business behaviour. Although time and context may have changed, the core of ethical problems inherent in business remains. In recent years, increased public concerns about corporate ethics have seen extant ethical rules being codified into formal codes of ethics. As a crucial part of corporate discourse, a code of ethics of an organisation signals its ethical commitment to self-restraint and selfregulation. It is often observed that corporate codes are instituted only after some legitimacy-threatening events and that they are used as a strategy to restore trust and organisational legitimacy. The impetus for this study arose from a desire to provide an understanding of the discursive role of corporate codes of ethics in (re)claiming public trust and legitimacy in light of increasing challenges to corporate legitimacy. As corporate codes are taken as the basis for discourses designed to provide ethical guidance, they constitute an important means to uphold trust and legitimacy for organisations. The study examines 100 global corporate codes of ethics using a three-level analytical framework based on discourse theory to capture the relationship between the “text” and the “context” of the codes. In the process of discourse analysis, it explores the historical (inclusive of cultural, social, and economic) context of code development (macro level), employs institutional theory to interpret the institutional context of corporations (meso level), and examines the content/text of the codes (micro level) by drawing on Aristotle’s three rhetorical justifications (logos, ethos, and pathos) to ascertain how the sample companies persuade their audiences to accept their ethical commitments. There is evidence that the code language employed by the 100 sample global companies is sufficiently persuasive to support the pragmatic, cognitive, and moral legitimising causes. However, it is found that the content of codes is comparatively light in ethical substance as it tends to focus on behavioural constraints specifically designed to address the pressing legitimacy issues and the compliance of rules relating to these constraints.
Keywords: Business ethics